Hubungan Antara Pengintegrasian Teknologi Informasi dan Komunikasi Dalam Pembelajaran Dengan Hasil Belajar Matematika Peserta Didik - Otniel Likuayang; Mersty Elisabeth Rindengan; Jeanne Miera Mangangantung (STKIP Andi Matappa Pangkep, 2022)
The purpose of this quantitative study is to obtain information about the level of ICT integration in learning and student’s mathematics achievement, and at the same time to prove whether there is a significant relationship between the two variables. The respondents of the study were 90 grade five students who enrolled in second semester academic year 2021-2022, in one private school in North Minahasa. To collect the data needed for ICT integration in learning, the researcher distributed a self-construct questionnaire based on the theory of TAM, which was arranged according to Likert’s Scale with 5 alternative answers, from never to always. Meanwhile, the data of students’ mathematics achievement were based on the result of their mathematics exam. The result of the study showed that both ICT integration in learning and students’ Mathematics achievement were in moderate or sufficient categories. Moreover, the result proved that there is a significant relationship between ICT integration in learning and students’ Mathematics achievement. Therefore, it is recommended that Mathematics teachers implement ICT integration in learning because of the contribution it might give to maximize students’ Mathematics achievement.